The Basis of Atmospheric Mesoscale Dynamics and a Dynamical Method of Predicting Rainstorms - Gao, Shouting (Cambridge Scholars Publisher, 2021)
This book serves to deepen the theoretical understanding of mesoscale dynamics and makes its basic concepts clear, reflecting new research results. It emphasizes important theories that have not been given enough attention in recent years, such as generalized potential temperature and the moist potential vorticity theory of non-uniform saturated moist atmospheres. By integrating theory with practice, the book also introduces the forecast method of rainstorms and other disastrous weathers using dynamic factors.This book can be used as a point of reference for operational forecasters, researcher.